Topographic Control of Wind- and Thermally Induced Circulation in an Enclosed Water Body - Jinichi Koue (Geosciences, 2025)
The dynamics of large lake circulations are strongly modulated by wind forcing, thermal gradients, and shoreline topography, yet their integrated effects remain insufficiently quantified. To address this, numerical simulations were conducted in Lake Biwa to clarify the mechanisms underlying wind- and thermally driven gyres, with a focus on the influence of bathymetric asymmetry. In wind-driven cases, zonal and meridional wind stress gradients were imposed, revealing that cyclonic wind shear generated strong surface vorticity (up to 2.0 × 10−6 s−1) in regions with gently sloped shores, while steep slopes suppressed anticyclonic responses. Cyclonic forcing induced upwelling in the lake center, with baroclinic return flows stabilizing the vertical circulation structure. In windless thermal experiments, surface temperature gradients of ±2.5 °C were applied to simulate seasonal heating and cooling. Cyclonic circulation predominated in warm seasons due to convergence and heat accumulation along gently sloping shores, whereas winter cooling produced divergent flows and anticyclonic gyres. The southern and eastern lake margins, characterized by mild slopes, consistently enhanced convergence and vertical mixing, while steep western and northern slopes limited circulation intensity. These results demonstrate that shoreline slope asymmetry plays a decisive role in regulating both wind- and thermally induced circulations, offering insights into physical controls on transport and stratification in enclosed lake systems.